PENGARUH PENGGANTIAN TEPUNG IKAN DENGAN TEPUNG MAGGOT (Hermetia Illucens) DALAM RANSUM AYAM PEDAGING TERHADAP KECERNAAN KALSIUM DAN FOSFOR - Pesik, Heince C.; Umboh, J. F.; Rahasia, C. A.; Pontoh, Ch. S. (ZOOTEC, 2016)
EFFECT OF SUBSTITUTION OF FISH MEAL WITH MAGGOT (Hermetia Illucens) MEAL ON CALCIUM (Ca) AND PHOSPHORUS (P) DIGESTIBILITY OF BROILER CHICKEN. As an animal feed, maggot from black soldier fly (Hermetia Illucens) has high calcium (Ca)  and phosphorus (P) content. Yet, little is known about the digestibility of calcium (Ca) and phosphorus (P) in the diet containing maggot. The present study was designed to determine the effect of substitution of fish meal with maggot (Hermetia illucens) meal in the diets on (Ca) and phosphorus (P) digestibility of broiler chicken. Twenty day old chicks (DOC) CP 707 broiler chicken of about 1300-1500 g body weight were assigned to each dietary treatment which was replicated four times in a Completely Randomized Design (CRD) arrangment. The experimental diet consisted of 5 treatments and 4 replications, formulated as follow: R0 = 100% fish meal  + 0% maggot meal; R1 = 75% fish meal + 25% maggot meal; R2 = 50% fish meal + 50% maggot meal; R3 = 25% fish meal + 75% maggot meal; and R4 = 0% fish meal + 100% maggot meal. Calcium (Ca) and phosphorus (P) digestibility were calculated using total collection method. Parameters measured were calcium (Ca) and phosphorus (P) digestibility. Differences were considered significant at P < 0.05. Tukey test (HSD) was employed to further analyze among treatment diferences. The results showed that calcium (Ca) digestibility was significantly (P < 0,05) increased as the level of maggot (Hermetia Illucens) meal in the diets increased; whereas the digestibility of phosphorus (P) was not significantly (P > 0,05) affected by the treatments. It can be concluded utilization of maggot (Hermetia illucens) meal up to 100% replaced fish meal or  15% in the diet, inreased calcium (Ca) digestibility and did not affect phosphorus (P) digestibility of broiler chicken.   Key words: Fish meal, Maggot (Hermetia Illucens) meal, Calcium and Phosphours digestibility